Edukasi Geografi dalam Analisis Dampak Lingkungan untuk Perencanaan Tata Ruang dan Wilayah Bagi Siswa SMA Ibnu Hajar Boarding School - Ramadhina, Sofi Auliya; Nurkhaerani, Fatma (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: This community service initiative aimed to enhance students' understanding of spatial planning and environmental impact analysis in regional development at SMA Ibnu Hajar Boarding School. Using participatory and educational approaches, the activity was conducted in three main stages: preparation, implementation, and evaluation. Method: The methods included interactive presentations, case studies, and simulations of sustainable spatial planning. Result: Survey results from 17 respondents revealed that 94.1% of students comprehended the material, with 35.3% rating it highly relevant to their prior learning. However, 5.9% of students required more varied approaches, such as interactive media or in-depth discussions. The activity successfully fostered critical thinking and environmental awareness among students, though challenges like diverse learning styles remain. Conclusion: Recommendations for future initiatives include adopting project-based methods and collaborating with relevant institutions to deepen students' understanding.